SEKOLAH ALAM: EVALUASI PROGRAM SEKOLAH DALAM MENUMBUHKAN KECERDASAN NATURALISTIK DAN KINESTETIK PADA PENDIDIKAN ANAK USIA DINI - Mukti, Taufiq Satria; Utami, Mutiara Arlisyah Putri; Puspitasari, Fantika Febry (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
Naturalist and kinestetic Intelligence in Early childhood become the main parameters in the stages of growth and development. This Intelligence becomes a strong foundation in the future in achieving self-success in the industrial era 4.0. In guarding the growth and development of early childhood, Sekolah Alam was an solutions to prpare for the golden generation in the future. Program evaluation carried out with the CIPP (Context Input Process Poduct) model approach aim to measures the achievement of the implementation of the organizing and outcome program for the students. The result showed that the implementation of the program was in the very good category 88,9% and outcome 87,5% student achievied the curriculum target, so it can be concluded that the Sekolah Alam curriculum was succesfully implemented to build the naturalist and kinesthetic intelligence.